Pijat Punggung dan Pemberian Aromaterapi Clarysage Terhadap Nyeri Persalinan Pada Ibu Bersalin - Fitriasnani, Meirna Eka; Prasetyanti, Dhita Kris; Mahmudah, Naufal (Universitas Nusantara PGRI Kediri, 2020)
Various efforts can reduce labor pain, both pharmacologically and non-pharmacologically. One non-pharmacological method is to use massage and aromatherapy which is cheaper, simpler, effective and without adverse effects. Pain is subjective for each individual, but if it is not resolved properly it will cause maternal morbidity, and will increase maternal mortality. The purpose of this study was to determine differences in the effectiveness of back massage and the administration of Clary Sage aromatherapy to labor pain in the active phase of the first phase of labor. The research design used was pre-experimental. The population studied was all mothers in the active phase of the first phase of 24 people with a purposive sampling technique with a sample of 10 people. The research instrument used was a numerical rating scale and observation sheet. The results of the study were analyzed using paired sample tests. The results of the study showed that most women who had back massages experienced moderate pain on a scale of 4, while those given Clary Sage aromatherapy experienced mild pain on a scale of 3. This is because massage stimulates the body to release endorphin compounds which are natural pain relievers . While clarysage aromatherapy can strengthen the respiratory system and muscles during labor, facilitate regular contractions, be effective to speed up the birth process, and reduce pain and tension. Based on the results of the analysis shows that there are differences in the effectiveness of back massage and the administration of Clary Sage aromatherapy to labor pain in the active phase of the first phase of labor.